2011
DOI: 10.1088/0953-8984/23/6/065401
|View full text |Cite
|
Sign up to set email alerts
|

Local order in layered NiPS3and Ni0.7Mg0.3PS3

Abstract: The family of two-dimensional magnetic materials M(II)PS(3) where M = Mn, Fe, Ni, Mg, Zn, etc shows a wide range of fascinating magnetic behaviour. It also shows potentially useful chemical properties including intercalation of nonlinear optical molecules and lithium ions. These properties are due to a crystal structure in which the ab planes are well-ordered in the plane but poorly correlated along c. Here, the short-range ordering is modelled in NiPS(3) and Ni(1 - x)Mg(x)PS(3) (x = 0.3). X-ray diffuse scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
5
20
0
Order By: Relevance
“…Following a similar vein of research, Goossens et al have looked at other important properties in the magnetic Ni 2 P 2 S 6 MTP compound and the diluted alloy Ni 1.4 Mg 0.6 P 2 S 6 and found that in the latter case, though the alloy formed an ordered solid solution, the ordering was imperfect in that the minority species was clustered into groups of 10–30 atoms. Considerations such as these must be taken into account when considering the application of a material in a nanoscale environment and could even allow for nanoscale engineering of ferroic and magnetic properties.…”
Section: Functionality and Applications Of Mtp Compoundsmentioning
confidence: 97%
See 2 more Smart Citations
“…Following a similar vein of research, Goossens et al have looked at other important properties in the magnetic Ni 2 P 2 S 6 MTP compound and the diluted alloy Ni 1.4 Mg 0.6 P 2 S 6 and found that in the latter case, though the alloy formed an ordered solid solution, the ordering was imperfect in that the minority species was clustered into groups of 10–30 atoms. Considerations such as these must be taken into account when considering the application of a material in a nanoscale environment and could even allow for nanoscale engineering of ferroic and magnetic properties.…”
Section: Functionality and Applications Of Mtp Compoundsmentioning
confidence: 97%
“…) with the ultimate aim of using this magnetic functionality for spintronic or magnetoelectronic applications . Investigations into MTP magnetic compounds have been numerous over the years (e.g (see Table 5 for a complete list of magnetic compounds).…”
Section: Functionality and Applications Of Mtp Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,50 To assess the effects on the band edge positions of single-layer APX 3 , we apply biaxial strains in the range from −4% to 4% on SL Ag 0. 5 CBM and VBM levels of SL Ag 0.5 In 0.5 PSe 3 are shown in Figure 7. In the region of strain, we observe that the band gap and the levels of CBM and VBM of SL CdPS 3 depend linearly on strain.…”
Section: Alignment Of the Cbm And Vbm Energies Of Single-layer Apxmentioning
confidence: 99%
“…Metal phosphorus trichalcogenides (APX 3 , A = M II , M I 0.5 M III 0.5 ; X = S, Se; M I , M II , and M III refer Group-I, Group-II, and Group-III metals, respectively) have been extensively studied due to their magnetic and ferroelectric properties. [5][6][7][8][9][10][11][12][13][14] And these compounds, as layered materials, also have potential applications in fields of hydrogen sorption, hydrogen storage, and lithium battery. [15][16][17] In layered crystalline materials, the interlayer coupling is the relatively weak van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%